2021
DOI: 10.1186/s12885-021-08989-w
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNA hsa_circ_0043278 inhibits breast cancer progression via the miR-455-3p/EI24 signalling pathway

Abstract: Background Breast cancer (BC) is one of the major malignancies worldwide. Circular ribonucleic acids (circRNAs) are a class of conserved ribonucleic acid (RNA) molecules that play important roles in various diseases. Recently, circRNAs have been suggested to have diagnostic value and may function as potential diagnostic biomarkers for BC. Previously, hsa_circ_0043278 was found to be downregulated in human BC. However, its role in human BC has not yet been identified. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…Furthermore, there has evidence that many circRNAs act as miR-455–3p sponges across cancer progression. For example, circ_0043278 sponges miR-455–3p to inhibit breast cancer 22 , circ_SEC24A sponging miR-455–3p and accelerates tumor progression 23 , and circ_CSNK1G1 acts as a molecular sponge for miR-455–3p to promote the progression of colorectal cancer 24 . Previous studies have confirmed that multiple circRNAs act as molecular sponges of miR-455–3p to regulate cancer progression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, there has evidence that many circRNAs act as miR-455–3p sponges across cancer progression. For example, circ_0043278 sponges miR-455–3p to inhibit breast cancer 22 , circ_SEC24A sponging miR-455–3p and accelerates tumor progression 23 , and circ_CSNK1G1 acts as a molecular sponge for miR-455–3p to promote the progression of colorectal cancer 24 . Previous studies have confirmed that multiple circRNAs act as molecular sponges of miR-455–3p to regulate cancer progression.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, circRNAs that act as miR-455-3p sponges and affect cancer progression have been identified. circ_0043278 can sponge miR-455-3p to regulate etoposide-induced gene 24 expression, thereby inhibiting breast cancer [22]. Circ _SEC24A accelerates tumor progression in hepatocellular carcinoma by sponging miR-455-3p to increase PPM1F expression [23].…”
Section: Introductionmentioning
confidence: 99%
“…Mechanistically, this circRNA by interaction with DEAH (Asp-Glu-Ala-His) box helicase 15 (DHX15) blocked DHX15-NF-κB p65 positive feedback loop, thereby suppressing breast cancer progression (69). Similar to circRNF10, hsa_circ_0043278 functions as a tumor suppressor gene, inhibits breast cancer progression by sponging miR-455-3p, increasing the level of EI24, reducing the activity of NF-κB pathway (70). Considering the role of RBPs in the biosynthesis of circRNA, a recent study indicated that tumor exosomal SERPINE2-derived hsa_circ_0001103 (cSERPINE2) was shuttled to tumor associated macrophages and remarkably increased MALT1, a vital regulator of immune responses, elevated the levels of IL-6 via stimulating NF-κB signaling, leading to promoting proliferation and invasion of breast cancer cells (71) (Figure 2).…”
Section: Breast Cancermentioning
confidence: 99%